2021
DOI: 10.1186/s12576-021-00815-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200c-3p promotes ox-LDL-induced endothelial to mesenchymal transition in human umbilical vein endothelial cells through SMAD7/YAP pathway

Abstract: Background Endothelial to mesenchymal transition (EndMT) participates in the progression of atherosclerosis (AS). MiR-200c-3p has been implicated in EndMT. However, the functional role of miR-200c-3p in AS remains largely unknown. Here, we demonstrated the critical role of miR-200c-3p in regulating EndMT in AS. Methods ApoE−/− mice were fed with high-fat diet to establish AS mouse model, and human umbilical vein endothelial cells (HUVECs) were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In the aortic tissues of ApoE −/− mice and oxLDL-treated HUVECs, miR-200c-3p was highly expressed. miR-200c-3p functions by inhibiting SMAD7 and YAP expression ( 64 ). In addition, LncRNA ZFAS1 was shown to upregulate Notch3 expression via miR-150-5p.…”
Section: Oxldl and Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…In the aortic tissues of ApoE −/− mice and oxLDL-treated HUVECs, miR-200c-3p was highly expressed. miR-200c-3p functions by inhibiting SMAD7 and YAP expression ( 64 ). In addition, LncRNA ZFAS1 was shown to upregulate Notch3 expression via miR-150-5p.…”
Section: Oxldl and Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…The arterial intimal hyperplasia is closely related to the transition of VSMCs from contractile phenotype to synthetic phenotype 25 and endothelial cell injury. 26 Through immunohistochemistry, we detected the positive expression of α-SMA, the marker of VSMCs with contractile phenotype and found that α-SMA-positive expression was considerably diminished in the HFC group compared with that in the SC group, and the number of α-SMA-positive cells was dramatically increased in the HFC + AM group compared with that in the HFC + AP group (all p < 0.01) (Figure 2(c)). Furthermore, Western blot revealed declined α-SMA protein level and CD31 (endothelial cell marker) and augmented level of OPN (the marker of VSMCs with synthetic phenotype) in the HFC group compared with those in the SC group, suggesting decreased number of VSMCs with contractile phenotype, increased number of VSMCs with synthetic phenotype, and exacerbated endothelial cell injury in the plaques of abdominal aorta of ApoE −/− mice on high-fat diet, while miR-663 overexpression jeopardized the phenotypic transition of VSMCs and attenuated endothelial cell injury (all p < 0.01) (Figure 2(d)).…”
Section: Resultsmentioning
confidence: 92%
“…Ox-LDL treatment similarly increased the expression of miR-200c-3p, and co-treatment of HUVECs with ox-LDL with miR-200c-3p potentiated the EndMT phenotype. This effect appeared to be mediated by miR-200c-3p inhibition of the SMAD7/YAP pathway [18].…”
Section: Endothelial To Mesenchymal Transition (Endmt) and Lipids And...mentioning
confidence: 91%
“…The micro-RNA, miR-200c-3p, is overexpressed in atherosclerotic aortic tissue. In the in-vitro experiments using HUVECs, treatment with oxidized LDL (ox-LDL) downregulated endothelial markers CD31 and vWF, while upregulating the mesenchymal markers ɑ-smooth muscle actin and vimentin [18]. Ox-LDL treatment similarly increased the expression of miR-200c-3p, and co-treatment of HUVECs with ox-LDL with miR-200c-3p potentiated the EndMT phenotype.…”
Section: Endothelial To Mesenchymal Transition (Endmt) and Lipids And...mentioning
confidence: 99%